2020
DOI: 10.3389/fimmu.2020.00483
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chemokine—Glycosaminoglycan Interactions to Inhibit Inflammation

Abstract: Leukocyte migration into tissues depends on the activity of chemokines that form concentration gradients to guide leukocytes to a specific site. Interaction of chemokines with their specific G protein-coupled receptors (GPCRs) on leukocytes induces leukocyte adhesion to the endothelial cells, followed by extravasation of the leukocytes and subsequent directed migration along the chemotactic gradient. Interaction of chemokines with glycosaminoglycans (GAGs) is crucial for extravasation in vivo. Chemokines need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 301 publications
(494 reference statements)
2
73
0
Order By: Relevance
“…Previous studies have demonstrated that over the course of RA, inflammatory cells migrate from peripheral blood to synovial tissues and secrete a variety of inflammatory factors, resulting in the destruction of the synovial membrane (27,28). Chemokines serve an important role in the infiltration and migration of inflammatory cells (29). CXCL12 is the only chemokine that binds to the receptor CXCR4 (30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that over the course of RA, inflammatory cells migrate from peripheral blood to synovial tissues and secrete a variety of inflammatory factors, resulting in the destruction of the synovial membrane (27,28). Chemokines serve an important role in the infiltration and migration of inflammatory cells (29). CXCL12 is the only chemokine that binds to the receptor CXCR4 (30).…”
Section: Discussionmentioning
confidence: 99%
“… 64 Since it is widely accepted that the binding of chemokine–GAG interactions also regulates the functioning of chemokines during injurious conditions, few researchers have investigated the inhibition of the GAG–chemokine axis along with the receptor–chemokine axis as an alternative strategy. 65 On this line, various small chemokine binding proteins (CKBPs) from many parasites and viruses, 66 immunomodulatory proteins such as evasins, 67 , 68 chemokine mimetics such as mutated and truncated chemokines, 69 aptamers, 70 and other small-molecule compounds binding to chemokines/receptors 71 , 72 have been identified as potential blockers/inhibitors of the GPCR/GAG–chemokine axis. Alternatively, the natural plant products such as flavonoids have been used to treat various injurious ailments, and due to their low toxic nature and safe consumption, they have drawn remarkable attention in new alternative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Specific patterns of chemokines are often found in the serum of patients with autoimmune diseases, but also in those with acute or chronic inflammatory diseases. In order to lure leukocytes to the site of inflammation, many chemokines form a gradient along the endothelial layer by binding to glycosaminoglycans, like heparan sulfate (15). In response to the chemokine gradient migratory leukocytes start rolling along the endothelial layer with the help of selectins that interact with low-affinity (16).…”
Section: Chemokines As Inflammatory Mediatorsmentioning
confidence: 99%